2014
DOI: 10.1103/physrevlett.113.246603
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Quantum Phases in Graphene with Enhanced Spin-Orbit Coupling: From the Quantum Spin Hall Regime to the Spin Hall Effect and a Robust Metallic State

Abstract: We report an intriguing transition from the quantum spin Hall phase to the spin Hall effect upon segregation of thallium adatoms adsorbed onto a graphene surface. Landauer-Büttiker and Kubo-Greenwood simulations are used to access both edge and bulk transport physics in disordered thallium-functionalized graphene systems of realistic sizes. Our findings not only quantify the detrimental effects of adatom clustering in the formation of the topological state, but also provide evidence for the emergence of spin a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…In theories and experiments regarding adatoms on the graphene, the size of adsorbed heavy metal nanoclusters or the coverage of adatoms is often considered [7,22,41,42]. After the first Bi-cluster deposition, the cluster coverage is low, as indicated by the 4.2% change in the resistance at room temperature.…”
Section: Coverage Effect Of Bi Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…In theories and experiments regarding adatoms on the graphene, the size of adsorbed heavy metal nanoclusters or the coverage of adatoms is often considered [7,22,41,42]. After the first Bi-cluster deposition, the cluster coverage is low, as indicated by the 4.2% change in the resistance at room temperature.…”
Section: Coverage Effect Of Bi Clustersmentioning
confidence: 99%
“…Several approaches have been suggested, such as utilizing the proximity effect in graphene/strong SOC material heterostructures [2][3][4], the hydrogenation and fluorination of graphene [5,6], and depositing certain heavy adatoms on graphene [7][8][9][10]. Experimentally, angle-resolved photoemission spectroscopy did not reveal an SOC gap in epitaxial Bi 2 Te 2 Se on chemical vapor deposition (CVD)- grown graphene [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while Kubo formula [29] offers fully quantum-mechanical treatment that can in principle capture all relevant effects, its standard analytical evaluation neglects [30] terms in the perturbative expansion in disorder strength which can become crucial for clusters of adatoms (such as those corresponding to skew-scattering from pairs of closely spaced impurities [31]). Finally the impact of unavoidable adatom clustering [32] onto graphene surface on θ sH is an open and important question, since adatom segregation has been shown to strongly affect spin transport properties [33,34].…”
mentioning
confidence: 99%
“…Therefore, this effect is particularly relevant in materials promising for valleytronics, such as graphene and TMDs. Furthermore, we would like to point out that it also provides important insight into another topic in which adatoms have been proposed to engineer the properties of graphene, such as spin-orbit coupling [32][33][34][35][36] and magnetism [37][38][39][40]. Despite many theoretical proposals, transport studies have shown that Au, Mg and In adatoms on graphene generate only long-range Coulomb impurity scattering, while neither spin-orbit scattering nor magnetic scattering has been introduced [41][42][43][44].…”
mentioning
confidence: 99%